Alkaline Treatment Of 3D Printed TI-AL-V Alloy For Bioactivity Surface Modification - Mohd Azman, ‘Aisyah Mardhiah (Universiti Sains Malaysia, 2022)
Ti6Al4V alloy has low bioactivity and surface treatment could improve its bioactivity. However, Ti6Al4V alloy manufactured by 3D printing has very fine microstructure compared to conventional manufacturing method. Thus, the aim of this work is to investigate the feasibility of modifying the surface of 3D printing Ti6Al4V alloy using NaOH alkaline treatment. . 3D printed Ti6Al4V alloy manufactured by 3D Gens Sdn Bhd in disc shape were soaked in 10M sodium hydroxide (NaOH) at 60ºC for 24hrs. Post heat treatment was applied to observe heating temperature affect upon the alkaline treated alloy at 200ºC, 400ºC, 600ºC and 800ºC. The X-Ray diffraction shows the presence of amorphous titanate layer after immersion in NaOH . The titanate was observed at 200ºC with the formation of rutile TiO2 after heat treatment at 800ºC. Morphology observation under Field Emission Scanning Electron Microscopy (FESEM) and elemental analysis indicate the deposition of titanate layer when heat treated with high temperature. The bioactivity of sample alkaline-heat treated at 200°C was investigated through immersion in Hank’s solution for 7 days trace 0.34wt% of Ca on alloy surfaces. The surface roughness of the sample after heat treatment was analysed using AFM where sample treated with 800ºC exhibit the highest surface roughness and alkali-heat treated at 200ºC has the lowest surface roughness. The wettability of the sample was tested by recording the contact angle of the sample with droplet of ultrasonic water where sample after alkaline treatment has the lowest value indicating it has the highest hydrophilic properties. The findings suggests that lower temperature after alkaline soaking is required to prevent phase transformation of sodium titanate layer during the post heat treatment so that high sodium titanate layer can form higher appetite layer on the surface alloy.